2015
DOI: 10.4172/2161-038x.1000156
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Wheat Sprout on Testicular Toxicity in Male Rats Exposed to Lead

Abstract: Objective: Negative effects of lead on the male reproductive system and sperm fertility parameters have been shown broadly. In recent years, use of medicinal herbs in reducing heavy metal toxicities has increased worldwide. One of these herbals, wheat sprout, contains high amount of vitamins (especially vitamin E), antioxidants and phytoestrogen compounds. This study investigated the effects of wheat sprout extract (WSE) and vitamin E on testicular oxidative stress in rats exposed to lead acetate.Methods: Thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…A significant increase in Malondiadehyde level was observed in female cavies exposed to lead acetate in the present study. These results are in line with the observations of Adibmoradi et al (2015) after lead acetate administration. The significant increase in MDA level suggests that oxidative stress is a major mechanism of the effect of lead in organism.…”
Section: Discussionsupporting
confidence: 92%
“…A significant increase in Malondiadehyde level was observed in female cavies exposed to lead acetate in the present study. These results are in line with the observations of Adibmoradi et al (2015) after lead acetate administration. The significant increase in MDA level suggests that oxidative stress is a major mechanism of the effect of lead in organism.…”
Section: Discussionsupporting
confidence: 92%
“…Means of the spermiogenesis index (SI) and the tubal differential index (TDI) were considered for the evaluation of spermatogenesis. For the TDI index, the ratio of seminiferous tubules with four or more lines of differentiated cells of type A spermatogonia was calculated, while the ratio of seminal tubules containing spermatids was calculated for the SI index [26].…”
Section: Histomorphometric and Histochemicalmentioning
confidence: 99%
“…It has been shown that antioxidants can prevent or reduce the oxidation of other molecules by ROS in a tissue or cell organisms, scavenge free radicals and attenuate their deleterious effects ( 11 12 ). Antioxidant activity or inhibition of generation of free radicals plays a crucial role in protection against such testicular toxicity.…”
Section: Introductionmentioning
confidence: 99%